Text analysis: linguistics, Semantics, Pragmatics in the Cognitive Approach - Kharlamov, A.A.; Yermolenko, T.V. (Управляющие системы и машины, 2015)
The cognitive approach to linguistic information analyzed by the human is considered. The processes of information processing are studied at various linguistic levels: morphological, lexical, syntactic and semantic levels for separate sentences, and finally, semantic and pragmatic levels for the text as a whole. As an example of the following processing, representation of the pragmatic level is identified as a chain of extended predicate structures of a particular text processing, pragmatic processing, chain of extended predicate structures.